Projective matrix representations of finite groups - Stoika Myroslav; Sztojka Miroszláv; Стойка Мирослав (ЗУІ ім. Ференца Ракоці ІІ, 2025)
Abstract. The classification of tame and wild finite groups G over a field R is completely solved in [1]. For a ring R, this problem is completely solved in specific cases when R is a ring of p-adic numbers or a complete discrete valuation ring or a ring of formal power series with P-adic coeficients (see [1]–[6]). In many other scenarios, solutions exist under certain restrictions on the groups or rings involved. We consider the case when G is a p-group and R is local ring of characteristic 0.
Keywords: finite groups; matrix